2015
DOI: 10.1017/jfm.2015.276
|View full text |Cite
|
Sign up to set email alerts
|

An active feedback flow control theory of the axisymmetric vortex breakdown process

Abstract: An active feedback flow control theory of the axisymmetric vortex breakdown process in incompressible swirling flows in a finite-length straight circular pipe is developed. Flow injection distributed along the pipe wall is used as the controller. The flow is subjected to non-periodic inlet and outlet conditions where the inlet profiles of the axial velocity, circumferential velocity and azimuthal vorticity are prescribed, along with no radial velocity at the outlet. A long-wave asymptotic analysis at near-crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The modes of the temporal-azimuthal Fourier series decomposition, extracted using frequency selection, are displayed as axial velocity isocontours to provide an overview of their structures in Figs. [13][14][15][16]. The juxtaposition of these structures with the cascade of the amplitude Fourier spectra (Fig.…”
Section: Temporal-azimuthal Fourier Series Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…The modes of the temporal-azimuthal Fourier series decomposition, extracted using frequency selection, are displayed as axial velocity isocontours to provide an overview of their structures in Figs. [13][14][15][16]. The juxtaposition of these structures with the cascade of the amplitude Fourier spectra (Fig.…”
Section: Temporal-azimuthal Fourier Series Modesmentioning
confidence: 99%
“…This interpretation was further validated by the global stability analysis of a nonparallel flow by solving the eigenvalue problem of the 3D linearized Navier-Stokes [9] equations around a base flow (see [10,11]). The vortex breakdown stemming from a Grabowski-Berger vortex in an open geometry has become a benchmark model for disturbance analysis (see [12,13]).…”
Section: Introductionmentioning
confidence: 99%
“…We also conducted numerical simulations of the flow dynamics based on (2.3), (2.4a) and (2.4b) and the assumed boundary conditions. These simulations are based on a modified code of Rusak et al (2012) and Rusak, Granata & Wang (2015), which includes the viscous terms and axial periodic boundary conditions. For the case of a base flow with β = 1 and 0 < α < 1, we used various initial conditions given by…”
Section: Solid-body Rotation Flow Between Two Coaxial Rotating Cylindersmentioning
confidence: 99%
“…Tănasă et al (2013) used a flow-feedback method with the water taken from downstream in the draft tube to keep the nominal discharge constant. Rusak, Granata, and Wang (2015) studied a flow injection distributed along a finite-length straight circular pipe wall to control the vortex breakdown process in incompressible axisymmetric swirling flows. They demonstrated that applying the proposed control method during flow evolution is successful in eliminating the breakdown states.…”
Section: Introductionmentioning
confidence: 99%